FOETAL for NCD—FOetal Exposure and Epidemiological Transitions: the role of Anaemia in early Life for Non-Communicable Diseases in later life: a prospective preconception study in rural Tanzania. Issue 5 (22nd May 2019) - Hjort, Line; Lykke Møller, Sofie; Minja, Daniel; Msemo, Omari; Nielsen, Birgitte Bruun; Lund Christensen, Dirk; Theander, Thor; Nielsen, Karsten; Larsen, Lise Grupe; Grunnet, Louise Groth; Groop, Leif; Prasad, Rashmi; et al.
Abstract : Purpose: Low-income and middle-income countries such as Tanzania experience a high prevalence of non-communicable diseases (NCDs), including anaemia. Studying if and how anaemia affects growth, placenta development, epigenetic patterns and newborns' risk of NCDs may provide approaches to prevent NCDs. Participants: The FOETALforNCD (FOetal Exposure and Epidemiological Transitions: the role of Anaemia in early Life for Non-Communicable Diseases in later life) Study is a population-based preconception, pregnancy and birth cohort study (n=1415, n=538, n=427, respectively), conducted in a rural region of North-East Tanzania. All participants were recruited prior to conception or early in pregnancy and followed throughout pregnancy as well as at birth. Data collection included: maternal blood, screening for NCDs and malaria, ultrasound in each trimester, neonatal anthropometry at birth and at 1 month of age, cord blood, placental and cord biopsies for stereology and epigenetic analyses. Findings to date: At preconception, the average age, body mass index and blood pressure of the women were 28 years, 23 kg/m 2 and 117/75 mm Hg, respectively. In total, 458 (36.7%) women had anaemia (haemoglobin Hb <12 g/dL) and 34 (3.6%) women were HIV-positive at preconception. During pregnancy 359 (66.7%) women had anaemia of which 85 (15.8%) women had moderate-to-severe anaemia (Hb ≤9 g/dL) and 33 (6.1%) women had severe anaemia (Hb ≤8 g/dL). In total, 185 (34.4%) women were diagnosed with malaria during pregnancy. Future plans: The project will provide new knowledge on how health, even before conception, might modify the risk of developing NCDs and how to promote better health during pregnancy. The present project ended data collection 1 month after giving birth, but follow-up is continuing through regular monitoring of growth and development and health events according to the National Road Map Strategic Plan in Tanzania. This data will link fetal adverse event to childhood development, and depending on further grant allocation, through a life course follow-up.